Continuous twin screw granulation: Impact of microcrystalline cellulose batch-to-batch variability during granulation and drying - A QbD approach - Christoph Portier; Tamas Vigh; Giustino Di Pretoro; Jan Leys; Didier Klingeleers; Thomas De Beer; Chris Vervaet; Valérie Vanhoorne (Elsevier, 2021)
Despite significant advances in the research domain of continuous twin screw granulation, limited information is currently available on the impact of raw material properties, especially considering batch-to-batch variability. The importance of raw material variability and subsequent mitigation of the impact of this variability on the manufacturing process and drug product was recently stressed in the Draft Guidance for Industry on Quality Considerations for Continuous Manufacturing by the U.S. Food and Drug Administration (FDA). Therefore, this study assessed the impact of microcrystalline cellulose (MCC) batch-to-batch variability and process settings in a continuous twin screw wet granulation and semi-continuous drying line. Based on extensive raw material characterization and subsequent principal component analysis, raw material variability was quantitatively introduced in the design of experiments approach by means of t1 and t2 scores. L/S ratio had a larger effect on critical granule attributes and processability than screw speed and drying time. A large impact of the t1 and t2 scores was found, indicating the importance of raw material attributes. For the studied formulation, it was concluded that MCC batches with a low water binding capacity, low moisture content and high bulk density generated granules with the most desirable quality attributes. Additionally, an innovative and quantitative approach towards mitigating batch-to-batch variability of raw materials was proposed, which is also applicable for additional excipients and APIs.